The ideal of celibacy in Platonism: from Plato to Plotinus (Actual Problems of Mind, 2017)
The paper explains conceptual sources, philosophical foundations and the key stages in developing the celibacy ideal in Platonism, which has inﬂuenced the formation of the ascetic traditions of a «spiritual» spousal between the human soul and God in Christianity, as well as the traditions of a «spiritual» family.
Keywords: Celibacy; platonism; orphism; asceticism; "spiritual" marriage; philosophical contemplation